THE LANDSCAPE OF YOUTUBER KIAI MOVEMENTS: RADICAL AND MODERATE - Moh Miftah Farid (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
In today's era of modern technology, the dissemination of da'wah has become highly widespread through new media, including YouTube. This means that many da’i or Islamic scholars (kiai) are now using this popular platform to share various da'wah content based on their respective educational backgrounds. Nowadays, da'wah content is easily accessible and can be watched simply by clicking on the desired title, which then presents a menu of da'wah content representing different ideological streams. Therefore, it is important to recognize that on YouTube, there are Kiai YouTubers who adhere to either radical or moderate ideologies. This phenomenon has sparked the researcher’s interest to analyze and map which Kiai YouTubers fall under radical or moderate streams. The research focuses on (1) How is the landscape of radical Kiai YouTubers shaped? (2) How is the landscape of moderate Kiai YouTubers shaped?. The objectives of the research are (1) To identify the landscape of radical Kiai YouTubers. 2) To identify the moderate Kiai YouTubers. The research uses a qualitative approach with Ferdinand de Saussure’s semiotic analysis. The data sources consist of da’wah content from both radical and moderate Kiai YouTube channels. Data collection techniques include document analysis and audiovisual materials. Data analysis employs Ferdinand de Saussure’s semiotic theory. The validity of the data is ensured through prolonged observation, source triangulation, and adequate referencing. The results of this study identified five radical Kiai YouTubers: Kiai Yazid Jawas, Kiai Abdul Hakim bin Amir, Kiai Ahmad Zainuddin, Kiai Subhan Bawazier, and Kiai Fatih Karim. Additionally, five moderate Kiai YouTubers were also identified: Kiai Bahauddin Nursalim, Kiai Adi Hidayat, Kiai Quraish Shihab, Kiai Husein Ja’far, and Kiai Said Aqil Siradj.